STRATEGI PENGEMBANGAN KOPERASI SYARIAH BERBASIS TEKNOLOGI FINANSIAL DENGAN PENDEKATAN INTERPRETATIF STRUCTURAL MODELLING (STUDI KASUS: KKSPN, KOTA BUKITTINGGI) - Laila Sari; Yenty Astarie Dewi (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
This study aims to formulate a development strategy for Islamic cooperatives based on financial technology (fintech), using a case study of the Civil Servants’ Sharia Consumer Cooperative (KKSPN) in Bukittinggi City. Despite KKSPN's large asset base, its financial management still relies on manual Excel-based systems, which are prone to input errors and data loss. This indicates a gap between the potential for digitalization and the readiness of members and infrastructure. Using the Interpretative Structural Modelling (ISM) approach, this research maps the interrelations among elements influencing the development of digital financial systems, through the construction of a Structural Self-Interaction Matrix (SSIM), Reachability Matrix, and hierarchical structure. The results show that fintech adoption in KKSPN must be carried out gradually by considering human resource readiness, member needs, and technological infrastructure. ISM proves to be effective in assisting the development of a sustainable digitalization roadmap for Islamic cooperatives. Proper fintech implementation can improve operational efficiency, data transparency, and service quality for members. These findings contribute practically by providing a model for designing Islamic cooperative information systems that align with local contexts and user preferences, and theoretically by demonstrating the relevance of ISM in developing Sharia-based microfinance institutions.